Parent knowledge of and attitudes towards youth sport-related concussion and associations with child and parent factors - Samantha D Roberts; Phillip Schatz; Johna Register-Mihalik; Magdalena Wojtowicz (Concussion, 2022)
Aim: This cross-sectional study aimed to better understand parental knowledge and attitudes regarding pediatric sport-related concussions, and association with parent/child biopsychosocial factors....